Diabetes-related cognitive impairment: Mechanisms, symptoms, and treatments - Yu Xueting; He Huimei; Wen Jie; Xu Xiuyuan; Ruan Zhaojuan; Hu Rui; Wang Fang; Ju Haibing (Open Medicine)
Diabetes-related cognitive impairment is increasingly recognized as a significant complication, profoundly impacting patients’ quality of life. This review aims to examine the pathophysiological mechanisms, clinical manifestations, risk factors, assessment and diagnosis, management strategies, and future research directions of cognitive impairment in diabetes.